Exploring Multilingualism to Inform Linguistically and Culturally Responsive English Language Education - Miriam Weidl; Elizabeth J. Erling (Education Sciences)
Linguistically and culturally responsive pedagogies (LCRPs) recognize students’ multilingual and cultural resources as central to inclusive and equitable learning. While such approaches are increasingly promoted in English language education (ELE), there remains limited understanding of the complexity of students’ multilingual trajectories—particularly in contexts marked by migration and linguistic diversity. This article addresses this gap by presenting findings from the Udele project, which explores the lived experiences of multilingual learners in urban Austrian middle schools. Using an embedded case study design, we draw on a rich set of qualitative methods—including observations, interviews, fieldnotes, student artifacts, and language portraits—to explore how two students navigate their linguistic repertoires, identities, and learning experiences. Our analysis reveals that students’ language-related self-positionings influence their classroom engagement and broader identity narratives. The findings demonstrate how shifts in self-perception affect participation and motivation, and how the students actively negotiate their multilingual identities within and beyond the classroom context. The complexity uncovered in their multilingual repertoires and life experiences underscores the critical need for longitudinal, multilingual research approaches to fully capture the dynamic and nuanced trajectories of language learners. These findings challenge prevailing conceptualizations of multilingualism in ELE, highlighting the importance of incorporating students’ lived linguistic experiences into pedagogical frameworks.